Relative Susceptibilities of ABO Blood Groups to Plasmodium falciparum Malaria in Ghana - Richmond Afoakwah; Edmond Aubyn; James Prah; Ekene Kwabena Nwaefuna; Johnson N. Boampong (Advances in Hematology)
The clinical outcome of falciparum malaria in endemic areas is influenced by erythrocyte polymorphisms including the ABO blood groups. Studies have reported association of ABO blood group to resistance, susceptibility, and severity of P. falciparum malaria infection. Individuals with blood group “A” have been found to be highly susceptible to falciparum malaria whereas blood group “O” is said to confer protection against complicated cases. We analyzed samples from 293 young children less than six years old with malaria in the Korle-Bu Teaching Hospital in Accra, Ghana. It was observed that group O was present in about 16.1% of complicated cases weighed against 40.9% of uncomplicated controls. Individuals with complicated malaria were about twice likely to be of blood groups A and B compared to group O (A versus O, OR = 1.90, 95% CI = 1.59–2.26, P<0.0001; B versus O, OR = 1.82. 95% CI = 1.57–2.23, P<0.0001). Blood group O participants with complicated diseases had low parasitaemia compared to the other blood groups (P<0.0001). This may give blood group O individuals a survival advantage over the other groups in complicated malaria as suggested. Participants with complicated falciparum malaria were generally anaemic and younger than those with uncomplicated disease.